Publics’ Perceptions of Community Pharmacists and Satisfaction with Pharmacy Services in Al-Madinah City, Saudi Arabia: A Cross Sectional Study - Amal A. El-Kholy; Khaled Abdelaal; Hussain Alqhtani; Basel A. Abdel-Wahab; Mohamed M. M. Abdel-Latif (Medicina, 2022)
Background and Objectives: Pharmacists play a major role in serving patients and delivering pharmaceutical services to the community. It is unclear whether the public fully appreciates what pharmacists can do as key health care providers. This study aims to examine public perceptions of community pharmacists and levels of satisfaction with pharmacy services. Materials and Methods: A cross-sectional study was conducted on a randomly selected sample population (n = 1000) in Saudi Arabia over a period of six months from January through June 2019. A 40-item, structured, self-administered questionnaire was used, comprised of questions on the demographics characteristics of the respondents and their satisfaction with pharmacy services. Descriptive statistics were used to analyze the data. Results: The response rate of the survey was 76.92%. Public opinions were influenced by pharmacists’ availability and knowledge, service promptness, and counseling services. Overall, 80.5% of respondents agreed that community pharmacists treat them with respect. Doctors were identified as the preferred source of drug therapy consultation by 58.7% and pharmacists by 41.29%. About 72.8% of respondents agreed that pharmacists provided them with clear instructions about medication use, and 70.2% trusted pharmacists’ opinions about medications. About 62.5% of respondents expressed satisfaction with pharmacists, and 64.8% with pharmacy services. Conclusions: Customers’ opinions were influenced by pharmacists’ availability and knowledge, pharmacy service promptness, pharmacy location, waiting area, medication knowledge, and counseling. However, the public was greatly satisfied with community pharmacists’ professionalism and pharmaceutical services. This positive perception provides an opportunity for pharmacists to extend their roles as healthcare professionals.